Minimally Invasive Dentistry: Step by Step of an Anterior Adhesive Bridge - Ramírez Barrantes, Juan Carlos (2022)
Fixed Partial Dentures (PPF/FPD) bonded with resin cement are viable alternatives based on the fundamentals of Minimally Invasive Dentistry (MIO). The conservative concept of preserving healthy dental tissue allows planning a minimally invasive restorative approach. Nowadays, remain uncertain how to replace teeth in patients with edentulous spaces that are not suitable for implant placement or with limited economic factors. The current ceramic systems provide greater bond strength to the substrate while offering an optimal aesthetic result. Clinical and laboratory investigations demonstrate the adequate long-term clinical performance of fixed partial dentures bonded with resin cement. The present clinical case will be approached in an even more conservative way, without the unnecessary removal of healthy dental tissue, replacing a tooth with a unitary fixed partial prosthesis in a patient not suitable for the placement of endosseous implants.